Reassessing the effect of growth options on leverage - Ogden, Joseph P.; Wu, Shanhong (Journal of Corporate Finance, 2013)
Results of empirical studies of the trade-off theory of capital structure indicate that an important, stable factor is missing from traditional leverage regression models. Our review of theory leads us to the hypothesis that the missing factor is related to profitable growth options (GOs). Specifically, the relationship between optimal leverage and the market-to-book assets ratio (MB), a measure of GOs, is negative and highly convex. In tests of static trade-off theory, we find that a convex (inverse exponential) transformation of MB substantially increases adjusted R2 in leverage regressions, and partially subsumes the explanatory power of median industry leverage. Using the transformed MB variable also yields stronger results in tests of dynamic trade-off theory, including analyses of leverage evolution, speed of adjustment, and external financing activity.